2023
DOI: 10.3390/agronomy13051297
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Machine Learning Algorithms for Optimizing Maize Yield Forecasting in Central Europe

Abstract: Artificial intelligence, specifically machine learning (ML), serves as a valuable tool for decision support in crop management under ongoing climate change. However, ML implementation to predict maize yield is still limited in Central Europe, especially in Hungary. In this context, we assessed the performance of four ML algorithms (Bagging (BG), Decision Table (DT), Random Forest (RF) and Artificial Neural Network-Multi Layer Perceptron (ANN-MLP)) in predicting maize yield based on four different input scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Numerous studies have emphasized the importance of larger and more diverse datasets to improve the accuracy of machine learning models in agriculture [21], [22]. Furthermore, other studies have highlighted the need for more precise and detailed climate data to enhance the performance of predictive models for crop production [23], [24]. Our study supports these findings and emphasizes the need for continued efforts to collect and provide data suitable for machine learning analysis to improve crop yield prediction and management.…”
Section: Discussion Of the Resultssupporting
confidence: 81%
“…Numerous studies have emphasized the importance of larger and more diverse datasets to improve the accuracy of machine learning models in agriculture [21], [22]. Furthermore, other studies have highlighted the need for more precise and detailed climate data to enhance the performance of predictive models for crop production [23], [24]. Our study supports these findings and emphasizes the need for continued efforts to collect and provide data suitable for machine learning analysis to improve crop yield prediction and management.…”
Section: Discussion Of the Resultssupporting
confidence: 81%
“…Winston Pinheiro collected 1048 coffee bean samples for special and conventional coffee beans and obtained 97% and 88% prediction accuracy for SVM and RF, respectively [38]. With the large number of parameters computed during the training of the MLP [69], the study demonstrated low accuracy under small sample conditions. On the other hand, the computational efficiency advantage of SVM will promote its application in large survey area applications.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Artificial neural networks have gained significant attention due to their ability to mimic the functioning of the human brain and their effectiveness in solving complex problems [31]. The Multi-Layer Perceptron-based RNA model is a supervised learning algorithm and consists of multiple layers of interconnected nodes, with each node performing a simple calculation using a weighted sum of its inputs and an activation function [32]. The standard Weka parameters were maintained with a learning rate of 0.3, a batchsize of 100 and cross-validation with 10 folds.…”
Section: Model Description and Performance Analysismentioning
confidence: 99%